(untitled) (Bulletin of Armenian Libraries, 2023)
The presentation aims to briefly describe Armenian printing history and the development process. Based on the study of the sources, the role of Armenian publishing centers in the XVI-XXI centuries in the development of printed heritage, culture, education, science and civilization in Armenia, the Armenian diaspora and Artsakh are presented and evaluated. The presentation discussesand evaluates the conferences dedicated to Armenian printing, which is extremely important scientifically. Various bibliographic publications created during the development of printing will be discussed. The talk evaluates the role of libraries not only as strategic centers for the preservation of cultural heritage, but also their bibliographic activities as the most important means of describing, distributing and communicating documentary information sources. For a sustainable future, the talk highlights the importance of ensuring Armenian cultural heritage preservation by returning Armenian libraries (Armenian books and library collections) to Armenians, which are under the control of Azerbaijanis as a result of the 44-day Artsakh war (27 September - 9 November, 2020).